Phylogenetic and nucleotide sequence analysis of influenza A (H1N1) HA and NA genes of strains isolated from Saudi Arabia - Ahmed Ali Al-Qahtani; Muhammad Mubin; Damian M. Dela Cruz; Sahar Isa Althawadi; Muhammad Shah Nawaz ul Rehman; Marie Fe F. Bohol; Mohammed N. Al-Ahdal (Journal of Infection in Developing Countries)
Introduction: In early 2009, a novel influenza A (H1N1) virus appeared in Mexico and rapidly disseminated worldwide. Little is known about the phylogeny and evolutionary dynamics of the H1N1 strain found in Saudi Arabia. Methodology: Nucleotide sequencing and bioinformatics analyses were used to study molecular variation between the virus isolates. Results: In this report, 72 hemagglutinin (HA) and 45 neuraminidase (NA) H1N1 virus gene sequences, isolated in 2009 from various regions of Saudi Arabia, were analyzed. Genetic characterization indicated that viruses from two different clades, 6 and 7, were circulating in the region, with clade 7, the most widely circulating H1N1 clade globally in 2009, being predominant. Sequence analysis of the HA and NA genes revealed a high degree of sequence identity with the corresponding genes from viruses circulating in the South East Asia region and with the A/California/7/2009 strain. New mutations in the HA gene of pandemic H1N1 (pH1N1) viruses, that could alter viral fitness, were identified. Relaxed-clock and Bayesian Skyline Plot analyses, based on the isolates used in this study and closely related globally representative strains, indicated marginally higher substitution rates than the type strain (5.14×10-3 and 4.18×10-3 substitutions/nucleotide/year in the HA and NA genes, respectively). Conclusions: The Saudi isolates were antigenically homogeneous and closely related to the prototype vaccine strain A/California/7/2009. The antigenic site of the HA gene had acquired novel mutations in some isolates, making continued monitoring of these viruses vital for the identification of potentially highly virulent and drug resistant variants.